Role of Water on the Rotational Dynamics of the Organic Methylammonium Cation: A First Principles Analysis - Ross D. Hoehn (1836382) (2019)
Understanding the degradation mechanisms of lead-halide perovskites (CH3NH3PbI3) under exposure to liquid/aerosol water is an essential problem within the photovoltaic community. Herein we investigate both the static and the dynamic properties of the methylammonuim cation (MA) as it coordinates with invading water molecules (MA.(H2O)n, n = 1, 2, 3, 4) using both stationary state quantum mechanics and first principle molecular dynamics simulations. Various solvation structures of MA were characterized by their stabilization energies, dipoles, and Maximally-Localized Wannier Function (MLWF) centers. Calculation – and analysis – of vibrational shifts in the IR spectral region were performed for hydrated complexes; the locations of3+ stretching vibrations allude to significant hydrogen bonding between MA and the water molecules. Through Fourier analysis of the rotational dynamics on several MA · (H2O)n complexes, we conclude that the water molecules dampen the rotational motion of the MA as the intermolecular bonds formed between the water molecules and the MA act to hinder the rotation of the cation; these findings give explanatory support to earlier computational observations of humidity effects on perovskites (i.e., CH3NH3PbI3) materials. This work is a step toward understanding the water-MA cation interaction in bulk perovskites, thus providing greater understanding of in situ instability/degradation of perovskite bulk materials. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-018-36900-4